Approaching the emergent conception of life - Sadłocha, Łukasz (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2015)
Review of: Stanisław Zięba, Życie. Koncepcja emergentystyczna (ang. Life: The Concept of Emergence), PWN, Warszawa 2013, ss. 390.